Pengaruh Corporate Governance Terhadap ManajemenLaba Perusahaan Yang Terdaftar Di Jakarta IslamicIndex Tahun 2012-2015 - , Fitriyani; , Dra. Wafiatun Mukharomah, MM (2017)
The aim of this research is to provide empirical evidence on the impact of corporate governance on earnings management. Corporate governance is measured by non excecutive director, institusional ownership, audit commitee's size. Discretionary accrual is the proxy of earning management. This research has 19 companies as samples that listed in Jakarta Islamic Index, selected using purposive sampling method, during the research periode 2012-2015. Data were analyzed using multiple regression method. Based on the result of analysis concluded that all components of corporate governance (non excecutive director) have significant effect on earning magement, institusional ownership, audit commitee's size no significant effect on earning magement.